Rhetorical Strategies and Speech Acts Analysis: A Linguistic Research on Indonesia’s Minister Speech Advocating for Palestine - Zainal Arifin Renaldo (ELT-Lectura, 2024)
This research is aimed at finding out the use of rhetorical strategies and speech acts in the speech delivered by the minister of foreign affairs during United Nations General Assembly regarding the conflict between Palestine and Israel. This research applies qualitative method. The data taken was in the form of text from H.E Retno LP Marsudi’s speech that emphasized the stance and the concern from Indonesia as a country which supports the freedom of the Palestine as well as condemning any kinds of genocide The result of this research showed that there were two linguistic features employed in the H.E Retno LP Marsudi’s speech i.e rhetorical strategies and speech act with the proportion of 32% for each Pathos Ethos, and 37% for Logos. Besides, the 5 speech acts were also found in this research with the proportion of 13% for assertive and declarative, 31% for directive, 25% for expressive, and 19% for commissive. This is to prove that rhetorical devices are considered to contribute to the overall persuasiveness and impact of the speech to help the speaker conveying the message effectively and build a comprehensive engagement to the audience.